Research Status of Control Strategy for Hybrid Electric Vehicle - He Xiaolu; Bao Jiusheng; Yin Yan; Ma Chi (Jixie chuandong)
The hybrid electric vehicles are the mature product that transits from conventional vehicles to electric vehicles and have a great development prospect. The typical transmission structure of series hybrid electric vehicles,parallel hybrid electric vehicles and series- parallel hybrid electric vehicles is briefly introduced.Then,relevant control strategies and their advantages and disadvantages are deeply discussed. Further,based on the conclusion and analysis of the existing hybrid vehicle control strategies,the optimization status of various control strategies respectively,such as regenerative braking optimization,fuzzy logic optimization,power system parameter optimization and dynamic coordination optimization are significantly described. Lastly,the development trend of control strategies for hybrid electric vehicles in the future is pointed out.